MP29: Community based naloxone usability testing. (May 2019) - VandenBerg, S.; Harvey, G.; Martel, J.; Gill, S.; McLaren, J.
Abstract : Background : In Alberta in 2016 more people died from an opioid overdose than from motor vehicle crashes. Naloxone is an opioid antagonist - it can reverse an opioid overdose for a period of 30 to 60 minutes. Naloxone kits are available free at emergency departments and community organizations around the province with training provided at the point of pickup. It is possible that training may be refused or may be forgotten and people are often left to rely solely on the instructions included in the kit. Human centred design can improve the way people interact with overdose instructions.Aim Statement: This study will measure the effectiveness and usefulness of prototype community naloxone kit instructions over a six month period of time (2018) in Calgary and Edmonton with the aim to use human centred design principles to improve the way people interpret emergency overdose response directions.Measures & Design : Information design experts engaged people with lived experience to provide a process map outlining the current role that educational materials and instructions for community naloxone kits play in responding to an opioid overdose. Alberta Health Services (AHS) Human Factors, in collaboration with AHS harm reduction developed the protocol and administered pre- and post-questionnaire and specific 'performance checkpoints' intended to measure effectiveness and usefulness. A simulated overdose including a mannequin, injection trainer and anatomical paper diagram was designed and a community naloxone kit with instructions setting was provided. Participants were recruited through harm reduction nurses with pre-existing clinical relationships (experienced group), family and friends of people who use opioids and general public (non-experienced) through the University of Alberta Faculty of Art and Design.Evaluation/Results: A total of 30 voluntary participants provided their informed consent and engaged in a simulated overdose scenario using a set of prototype instructions developed by a professional information designer. Through repeated data sampling, the following points were observed and will be integrated in the next iteration of design: It isn't clear to people what opioids are. It isn't clear to people that giving a dose of naloxone will not harm a person, especially if they have not overdosed. Almost none of the participants called 911. People seem to read pictures and text equally in the non-experienced group, but in the experienced group, typically read the pictures. Many participants stated that they knew how to do rescue breaths, but did not perform them correctly. Performing the procedure is a not the same as being asked about how to perform the procedure.Discussion/Impact: Even with new instructional prototypes, many participants identified components that were unclear or confusing. The experienced group made less mistakes than the non-experienced group. They seemed to be more invested or interested in saving a friend's life. These instructions will go through another round of design to incorporate feedback from end users. The final product will be part of a larger provincial emergency medicine initiative that includes participant led design and education around emergency response in opioid overdose settings.